Alterations of Photopic Negative Response of Multifocal Electroretinogram in Patients with Glaucoma. (January 2015) - Kaneko, Muneyoshi; Machida, Shigeki; Hoshi, Yuya; Kurosaka, Daijiro
Abstract Purpose: To determine the effect of glaucoma on the multifocal electroretinograms (ERGs) (mfERGs) elicited by low-frequency stimuli. Methods: Forty-four patients with open-angle glaucoma and 15 normal subjects were studied. The stimulus frequency was 6.25 Hz, and the stimulus was a circle with a 6.8° radius that was centered on the fovea (center). MfERGs were also elicited by a quarter of an annulus placed around the macula (superior/temporal; inferior/temporal; superior/nasal; and inferior/nasal quadrants). The radius of the inner border of the annulus was 6.8° and that of the outer border was 20°. The actual sensitivity was determined by standard automated perimetry. The thickness of the ganglion cell complex (GCC) was measured by optical coherence tomography. Results: The mfERGs consisted of a negative wave (N1) followed by a positive wave (P1), and followed by a slow negative wave (N2). There were no significant differences in the response densities of N1 and P1 between the normal control and glaucomatous eyes in any areas. The N2 response density was significantly reduced with the severity of glaucoma in the center. There was a significant reduction even at an early stage of glaucoma compared to control values. In the center, the N2 response density was significantly correlated with the GCC thickness and mean sensitivity. However, in other stimulus areas, there was no significant reduction of any components of the mfERGs. Conclusions: These results suggest that the N2 component of the slow-sequence mfERGs is affected by glaucoma in the central retinal area. Regional variations in the contribution of the retinal ganglion cell activity to the N2 should be considered when examining the mfERGs in glaucoma patients.